P13.10 Chemoattraction of glioma cells in a local hydrogel trap and immune control associated with improved survival and cognitive functions in a mouse model of glioblastoma resection. (9th September 2021) - Castel, H; Laillet De Montulle, E; Dubois, M; Ferracci, F; Mutel, A; Dembele, K; Desrues, L; Derrey, S; Langlois, O; Chever, O; Gandolfo, P; Morin, F
Abstract: BACKGROUND: Glioblastoma (GB) is the most aggressive brain primary tumor. The prognosis remains poor mainly due to the invasiveness of glioma cells, radio and/or chemoresistance and GB-induced immunosuppressive environment. Here, we propose to use a local delivery system based on a biocompatible hydrogel containing the chemopeptide urotensin II (hUII) or a biased synthetic analog DAB8-hUII, to "trap" GB cells, and/or to control immune cells expressing its G protein-coupled receptor UT, leading to tumor regression and neurological benefit, in a mouse model of GB resection. MATERIAL AND METHODS: In vitro, invasion towards UII/analog across different hydrogels or glue of human or murine GB-GFP cell lines was evaluated in Boyden chamber and cloning ring assays. In vivo GB cells were intrastriatally xenografted, then resected while hydrogel- or glue-containing UII/analog was injected in the cavity resection. Behavioral tests, brain immunohistochemical analyses and mouse survival were then investigated. RESULTS: In vitro, invasive capacity of human U87 and 42MG or murine GL261 and CT2A GB cells was stimulated by UII loaded into hydrogel-based hyaluronic acid supplemented with collagen or other chemicals, PNIPAAm-PEG, or thrombin-fibrin glue. In vivo, injection of UII- or DAB8-hUII-loaded glue into the cavity resection of GL261 and CT2A GB in C57BL/6 mice significantly improved survival compared with tumor and resected experimental conditions. Neurological status was also tested before and after GB resection. We found that GL261 and CT2A cell-bearing mice expressed altered spontaneous activity, emotion and cognitive functions. Intracavity injection of the glue improved resignation and anxiety and increased motor activity and cognition with a best cognitive recovery with hUII and DAB-8-hUII-loaded glue groups. Ex vivo brain analyses revealed high expression of UT and UII in some GB GFP-positive cells and macrophages within GB core and at the interface with the normal brain, GB cells expressing UT migrating along tortuous podocalyxin+ vascular components. In brains bearing hydrogel/hUII glue, vascularization appears modified and GFAP+ astrocytes and F4/80+ macrophages were highly recruited in the border of the cavity, compared with the other conditions. CONCLUSION: A local glue containing UII may trap GB cells and remodel the tumor microenvironment responsible for survival and cognitive improvements, providing new option in the therapeutic arsenal of GB.